Philo of Alexandria and the embassy to Gaius in the Chronicon Syriacum and Historia Dynasticarum of Bar Hebraeus. Transmission, Text and Translation (Circe de clásicos y modernos, 2020)
Our work offers a translation from Syriac and Arabic into Spanish of the news about the embassy to Gayo and Philo of Alexandria contained in Chronicon Syriacum and History Dynasticarum. For this, we have divided our study into two parts. In the first we will present the evidences for the embassy to Gaius and Philo. We will begin with a trace of the references related to this event in Greek, Latin and Syriac sources, especially Flaccus and Embassy to Gaius of Philo, Jewish Antiquities of Josephus, Ecclesiastical History of Eusebius, Chronicon of Jerome and Chronicon of Michael the Syrian. The data transmitted by each of these sources will be compared with the news recorded in the chronicles of Bar Hebraeus. In the second part we will make a synthesis of the structure of these Syriac and Arabic chronicles, and their corresponding translation and notes.
Keywords: Chronicon syriacum; Historia Dynasticarum; Bar Hebraeus; Philo of Alexandria; Embassy to Gaius